2021
DOI: 10.1007/s00595-021-02329-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on gastric cancer treatment in Japanese high-volume centers: a JCOG stomach cancer study group survey

Abstract: Purposes The spread of coronavirus disease 2019 (COVID-19) has affected socioeconomic and healthcare systems in many countries. Accordingly, many individuals may have canceled their annual health-check programs, including esophagogastroduodenoscopy, which would have resulted in lower numbers of newly diagnosed patients with gastric cancer in comparison to other times. Methods Questionnaires were distributed to 62 hospitals every week from May 2020 to August 2020 (total 744) through mailing lists of the Stomach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
4
15
1
Order By: Relevance
“…Previous studies have shown significant decreases in GC patients of older age, early CS, and curative treatment procedures. 10,[19][20][21][22][23][24] However, previous studies showed only in a small number of facilities or in foreign countries, therefore, we revealed that the trends were consistent in the tertiary medical region covering 2.9 million populations in Japan. In addition, the change rate of each diagnostic procedure has not been studied previously, for that reason, we analyzed and found that the monthly mean of GCs decreased especially in cancer screening.…”
Section: Discussionsupporting
confidence: 41%
“…Previous studies have shown significant decreases in GC patients of older age, early CS, and curative treatment procedures. 10,[19][20][21][22][23][24] However, previous studies showed only in a small number of facilities or in foreign countries, therefore, we revealed that the trends were consistent in the tertiary medical region covering 2.9 million populations in Japan. In addition, the change rate of each diagnostic procedure has not been studied previously, for that reason, we analyzed and found that the monthly mean of GCs decreased especially in cancer screening.…”
Section: Discussionsupporting
confidence: 41%
“…This does not necessarily indicate that each hospital was affected equally: a questionnaire survey for gastrectomy revealed that selected high‐volume centers in Japan were differently affected by COVID‐19, with the most significant effects being observed in Tokyo. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, a similar trend in the number of surgical cases was observed in areas with high infection rates and in the country as a whole. This does not necessarily indicate that each hospital was affected equally: a questionnaire survey for gastrectomy revealed that selected high‐volume centers in Japan were differently affected by COVID‐19, with the most significant effects being observed in Tokyo 26 …”
Section: Discussionmentioning
confidence: 99%
“…In Japan, a significant decrease in the mean number of stage I gastric cancer cases and an increase in the number of symptomatic gastric cancer patients were observed during the COVID-19 pandemic from March to December 2020 [ 6 ]. In another Japanese study, the number of gastrectomies was < 80%, and there was a 50% decrease from May to August 2020 in Tokyo when compared to the previous year as determined using questionnaires [ 7 ]. However, there is little clarity on how the COVID-19 pandemic affected patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%